Papel do TLR-4 na resposta inflamatória e resistência à insulina no tecido adiposo em condições de sobrecarga nutricional crônica - Francisqueti, Fabiane Valentini [UNESP] (2013)
The prevalence of obesity has increased over the past two decades , and this increase has been attributed to changes in dietary habit where the increase of fats and sugars prevails . It is a risk factor for cardiovascular disease and inflammatory process favors this context. But is not yet well understood the effect of time -consuming unbalanced diet on inflammation via Toll-like receptor 4 ( TLR - 4 ) and its association with metabolic abnormalities . Therefore the aim of this study was to test the hypothesis that increased exposure to a nutritional overload leads to increased expression of TLR-4 and this initiates the inflammatory response with consequent metabolic changes. Male Wistar rats ( n = 32 animals ) were used , with 30 days of age, who were randomly divided to receive control diet ( C ) or high fat + sugar water ( HFD ) for 6 to 24 weeks , totaling 4 groups independent experimental ( C6 , C24 , HFD6 , HFD24 n = 8 animals / group ) . The C mice fed standard rodent chow diet and HFD group a high-fat diet . Body weight , adiposity index (AI ) , hypertension , glucose and lipid profile , hormonal evaluation , inflammatory plasma was evaluated . Tumor necrosis factor -alpha ( TNF - α ) , interleukin 6 ( IL - 6 ) , transcription factor NFkB and Toll like receptor 4 : the adipose tissue indicators of inflammation were evaluated . At the end of 6 weeks, the animals showed higher AI , triglycerides , glucose , insulin, leptin and lower adiponectin compared to C6 , featuring a picture of metabolic syndrome . At the end of 24 weeks , in addition to metabolic changes , the animals showed increased expression of TLR - 4 , NFkB and inflammatory cytokines TNF - α and IL - 6 in adipose tissue . Thus, we conclude that a prolonged time consumption of a diet rich in sugar and fat aggravates the situation of metabolic syndrome , and trigger an inflammation via TLR - 4